The additional protection system of the three - phase bridge pulse width modulated inverter/ Mohamad Aris Ramlan - Ramlan, Mohamad Aris (1991)
The main objective of this project is to design and construct an additional fast respond and good selectivity protection system to protect a three-phase bridge inverter system against fault caused by overcurrent and high operating di/dt of the switching transistors. This additional protection system is necessary so as to increases the protection capability of the inverter system to enable to withstand any fault that could results in damaging the circuits semiconductor components particularly due to the instantaneous surge of current occur during the transistor turn-on time and by short circuits in the system. The main overcurrent protection of the inverter system is being provided by the crowbar protection circuits and a back-up protection by a semiconductor circuit breaker.